Episodes (1959) Entente Cordiale? - Kane, Angela (Edinburgh: Edinburgh University Press, 2007)
RESUMEN: This article investigates Episodes (1959), which was a co-production by the New York City Ballet and the Martha Graham Dance Company. It assesses the immediate and longer-term impact of the work, both conceptually and choreographically, and the extent to which it can be considered 'a historic meeting of two dance worlds', as the New York Post claimed at the time. The article also explores the motivations of the three key figures involved - George Balanchine and Martha Graham as co-choreographers, and Lincoln Kirstein, General Director of NYCB - and the different working practices of the two companies. It draws upon dancers' accounts of the co-production, including Paul Taylor who performed in Balanchine's choreography, and extensive correspondence between Graham's company and NYCB.